Effectiveness of Positive Thinking Skills on Improving the Relation of Veteran Father and his Daughter - M. Mallahi; F. Niknezhadi (Afarand Scholarly Publishing Institute, 2016)
Aims: In their mental growth steps, the children of veterans, due to their fathers' emotional and excitement avoidance, undergo current and continuous mental pressures and blows, leading to a reduction in their quality of life. The aim of this study was to investigate the effectiveness of the positive thinking skills on the improvement of the parent-child relationship in the female high-school students of the veterans' families. Materials & Methods: In the controlled pretest-posttest experimental study, 30 female high-school students of the veterans' families were studied in Isfahan in the academic year 2015-16. The subjects, selected by random cluster method, were divided into two groups including experimental (n=15) and control (n=15) groups. Data was collected by the parent-child survey (the father form). Eight 60-minute positive thinking skills training sessions were conducted in experimental group. No training session was conducted in control group. The posttest was conducted in both groups after the conduction of the training sessions. Data was analyzed by SPSS 16 software using one-variable covariance analysis test. Findings: At the posttest stage, the mean score of the parent-child relationship in experimental group (107.66±18.71) was significantly higher than control group (96.53±11.40; p<0.05). Conclusion: The training of positive thinking skills can improve the parent-child relationship in the adolescent girls of the veterans' families.